Fasting lipid and lipoproteins concentrations in pregnant women with a history of migraine. - Gelaye, Bizu (2015)
Migraine is associated with a number of cardiometabolic risk factors including abnormalities in lipid metabolism. However, little is known about these associations among pregnant migraineurs. We conducted the present study to evaluate the extent to which altered lipid profiles are associated with history of migraine among pregnant women.